2014
DOI: 10.1186/1475-2875-13-455
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of intermittent preventive treatment with sulphadoxine-pyrimethamine for malaria during pregnancy and pregnancy outcomes: a cross-sectional study in Geita district, North-Western Tanzania

Abstract: BackgroundMalaria infection during pregnancy is associated with adverse outcomes in sub-Saharan Africa (SSA). For this reason, the World Health Organization currently recommends intermittent preventive treatment of malaria in pregnancy (IPTp) with sulphadoxine-pyrimethamine (SP) at each scheduled antenatal care (ANC) visit. In Tanzania, the revised IPTp policy was adopted in 2013 but the level of uptake and its association with pregnancy outcomes remains unknown.MethodsA cross-sectional study was conducted amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
60
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(94 citation statements)
references
References 43 publications
23
60
11
Order By: Relevance
“…Additionally this study establishes a link between low supply of SP in ANC, knowledge about impact of placental malaria by pregnant women, and uptake of SP. These results support the observations by Marchant et al, 2008, Mpogoro et al, 2014, and Mubyazi and Bloch, 2014, who observed SP unavailability and low uptake of SP among women in Tanzania [13, 18, 19]. Low uptake of SP may increase risk of malaria parasitaemia and therefore placental malaria prevalence among pregnant women in endemic areas.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally this study establishes a link between low supply of SP in ANC, knowledge about impact of placental malaria by pregnant women, and uptake of SP. These results support the observations by Marchant et al, 2008, Mpogoro et al, 2014, and Mubyazi and Bloch, 2014, who observed SP unavailability and low uptake of SP among women in Tanzania [13, 18, 19]. Low uptake of SP may increase risk of malaria parasitaemia and therefore placental malaria prevalence among pregnant women in endemic areas.…”
Section: Discussionsupporting
confidence: 89%
“…IPT-SP is recommended for prophylaxis during pregnancy in Cameroon and has been available at no cost since 2006 [15]. SP has efficacy for 4–6 weeks after a single dose and improved outcomes are seen with repeated dosing [1618]. Based on this data and concerns about emerging resistance, WHO recommends provision of at least three doses of SP in ANC clinic; Cameroon transitioned from a 2-dose to a 3-dose recommendation for IPT-SP in 2012 [19–21].…”
Section: Introductionmentioning
confidence: 99%
“…This estimate is reflected in a study by Nkoka et al that used MDHS dataset [31]. Globally, studies have revealed that uptake of at least two doses of IPTp-SP is associated with number of ANC visits [5,22,[30][31][32][33][34][35][36][37][38][39], directly observed therapy (DOT) [5,30,38,40,41], residential area [22,30,42], age of woman [42], education level and socioeconomic status [43], parity [5,42], timing of initial ANC visit [5,31,44], knowledge about malaria/IPTp-SP [5,38] and stockouts of the commodity [5,38,45].…”
Section: Ninety-eight Percent Of Malaria Infections Are Caused By Plamentioning
confidence: 99%
“…In 2004, WHO recommended a minimum of two doses of IPTp with SP along side other malaria prevention and control approaches during pregnancy [19,20]. In October 2012, however, WHO updated the policy to at least three doses after acknowledgement from Evidence Review Group (ERG) that reviewed research evidence on efficacy of IPTp-SP and its adverse outcomes in preventing MiP [21][22][23][24][25][26]. The updated policy further says that IPTp with SP should be administered at each antenatal visit, with the first dose given early in the second trimester and successive doses administered at monthly intervals until the time of delivery [27].…”
Section: Ninety-eight Percent Of Malaria Infections Are Caused By Plamentioning
confidence: 99%